Wheelchair half-marathon and marathon performance - the `Oita International Wheelchair Marathon` 1983-2011 - Knechtle, B.; Lepers, R. (Journal of Human Sport & Exercise, 2013)
We compared participation and performance trends of individuals with disabilities competing in the half- and full-marathon in the `Oita International Wheelchair Marathon` from 1981 to 2011. The performance times decreased during the 1980`s until the middle 1990`s and stabilized thereafter for both half-marathoners and marathoners. The mean top five overall finishers times were 0:52±0:07 h:min for half-marathoners and 1:36 ±0:11 h:min for marathoners, respectively. The mean age of the finishers increased significantly (p < 0.01) by 0.51 year per annum for the half-marathoners and by 0.62 year per annum for the marathoners, respectively. There was a significant (p < 0.001) age effect on time performance for both distances. The best time performance was observed for the age comprised between 16 and 54 years for half-marathoners, and between 25 and 49 years for marathoners, respectively.